Antimicrobial activity and LC-MS data comparison from Lichen Parmotrema praesorediosum in Bangi, Selangor, Malaysia - Anis Asmi Azman; Nurul Nadiah; Andi Rifki Rosandy; Rozida Mohd Khalid; Muntaz Abu Bakar; Afnani Alwi; Nurkhalida Kamal (Penerbit Universiti Kebangsaan Malaysia, 2021)
The research study regarding antimicrobial activity of pure compounds and LCMS data comparison from extract of lichen Parmotrema praesorediosum in Bangi, Selangor, Malaysia. Antimicrobial activity of acetone, ethanol, and methanol extracts as well as five compounds, namely methyl divaricatinate, methyl haematommate, methyl chlorohaematommate, methyl β-orsellinate, and vinapraesorediosic acid from methanol extract were identified for the microbial activity against four bacterial species, Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus, Enterobacter aerogens, and Escerichia coli as well as two fungal species, Candida albicans and Candida parapsilosis based on standards. The determination of IC50 using minimal inhibitory concentration (MIC) by broth microdilution method was carried out. For acetone extract, 201 μg/mL concentration was required to inhibit 50% (IC50) growth of positive gram bacteria, S. aureus while the concentrations of 430 and 480 μg/mL were able to inhibit 50% (IC50) growth of C. albicans and C. parapsilosis, respectively. Ethanol and methanol extract as well as five pure compounds did not inhibit 50% (IC50) of bacterial and yeast growths. Five pure compounds were first reported to determine IC50 of minimal inhibitory concentration (MIC) from lichen, Parmotrema praesorediosum in Malaysia. The comparison of LC-MS data between ethanol and acetone extracts showed that there was a peak of the main compound, atranorin in the acetone extract, but was invisible in the ethanol extract where the main bond broke down and produced other compounds. Result of pure compounds from antimicrobial activity and LCMS data comparison from extract of lichen Parmotrema praesorediosum were first reported in Bangi, Selangor, Malaysia. Data produced from this study will be used to show the comparison and latest result that will provide ongoing body of research into the issue of natural product.